(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Taking into account the rapid pace of life in the modernization of small towns, the importance of organizing the process of educating children in the buildings of preschool educational organizations, as well as the object of design as an element of a multifunctional complex, the complex includes changes in its volumetric and functional compliance. In the architectural design of a preschool educational organization, functional-planning requirements are mainly taken into account in the formation of the structure and the development of the area of the premises.